Comprehensive index evaluation of the spontaneous combustion capability of different ranks of coal. (1st May 2021) - Wang, Cai-Ping; Zhao, Xiao-Yong; Bai, Zu-Jin; Deng, Jun; Shu, Chi-Min; Zhang, Min
Graphical abstract: Highlights: The indicator gas analysis method was substantially improved. The principle diagram of the low-temperature oxidation process of coal was drawn. The actual exothermic strengths of the coal samples were compared. The effect of the coal metamorphic degree on spontaneous combustion was determined. Abstract: To investigate the effect of coal metamorphism on the probability of coal spontaneous combustion (CSC), five types of coal sample were subjected to a temperature-programmed testing system. The gas indicators and limiting parameters of CSC were analysed and the characteristics of different ranks of coal were observed during low-temperature oxidation. The CO production rate of each coal sample was positively correlated with temperature and the CO production rate of low-ranked coal was greater than that of high-ranked coal. The CO/O2 and CO productivity trends were the same. Analysis of the change in the alkene ratio revealed that the oxidation reaction became more intense if the coal temperature exceeded the dry cracking temperature. The oxygen consumption rate of each coal sample was positively correlated with temperature, low-ranked coal samples exhibiting higher oxygen consumption rates. Graham's fire coefficient can be used as an auxiliary gas indicator to judge CSC tendency. Analysis of the limiting parameters of CSC revealed that the low limiting oxygen volume fraction and the minimal thickness of residual coal of high-rank samples were higher, whereas maximal air leakage intensity was lower. This paper further demonstrated differences in CSC tendency depending on the coal rank. These findings clarified certain factors affecting CSC, which may aid in preventing CSC in the future.